Meningkatkan Kinerja BUMN: Antiipasi Terhadap Kompetisi dan Kebijakan Deregulasi - Kumorotomo, Wahyudi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1996)
The problems concerning the state owned corporations are very closely related with the role of the national economy in development activities. Generally, the role of the national economy as reflected by the existence of the state owned enterprises is so, because oldie lack of the private sector to handle particular public problems. In Indenesio, the existence of :he state owned corporation is intended to manage the necessities of life for many people, as provided by Article 33 fine 1945 constitution. in developing the mission which must be handled by these state owned enterprises however, the role of the state owned corporations as agents of development is not achieved. This writing attemps to look normative concepts which must apply to the state owned corporations as public corporations and loosen the alternative criteria to evaluate the work of state owned corporations. Basing on this analysis, it can be concluded that the major role of the state owned enterprises in future is to shift to the provision of public services, but not the extraction of natural resources any more. For this reason therehre, standard for evaluating the work of these state owned corporations must also be developed relating to the dimensions of public services like: efficiency, effectiveness, justness and perception.